The Goddess - Mandakranta Bose,Ed (OUP, 2018)
The Oxford History of Hinduism: The Goddess provides a critical exposition of the Hindu idea of the divine feminine, or Devī, conceived as a singularity expressed in many forms. With the theological principles examined in the opening chapters, the book proceeds to describe and expound historically how individual manifestations of Devī have been imagined in Hindu religious culture and their impact upon Hindu social life. In this quest the contributors draw upon the history and philosophy of major Hindu ideologies, such as the Purāṇic, Tāntric, and Vaiṣṇava belief systems. A particular distinction of the book is its attention not only to the major goddesses from the earliest period of Hindu religious history but also to goddesses of later origin, in many cases of regional provenance and influence. Viewed through the lens of worship practices, legend, and literature, belief in goddesses is discovered as the formative impulse of much of public and private life. The influence of the goddess culture is especially powerful on women's life, often paradoxically situating women between veneration and subjection. This apparent contradiction arises from the humanization of goddesses while acknowledging their divinity, which is central to Hindu beliefs. In addition to studying the social and theological aspect of the goddess ideology, the contributors take anthropological, sociological, and literary approaches to delineate the emotional force of the goddess figure that claims intense human attachments and shapes personal and communal lives.